Emerging and innovative techniques for arsenic removal applied to a small water supply system - Duarte, António A. L. Sampaio (2009)
The impact of arsenic on human health has led its drinking water MCL to be drastically reduced from 50 to 10 ppb. Consequently, arsenic levels in many water supply sources have become critical. This has resulted in technical and operational impacts on many drinking water treatment plants that have required onerous upgrading to meet the new standard. This becomes a very sensitive issue in the context of water scarcity and climate change, given the expected increasing demand on groundwater sources. This work presents a case study that describes the development of low-cost techniques for efficient arsenic control in drinking water. The results obtained at the Manteigas WTP (Portugal) demonstrate the successful implementation of an effective and flexible process of reactive filtration using iron oxide. At real-scale, very high removal efficiencies of over 95% were obtained.